Ophiocordyceps sinensis preparations combined with the renin–angiotensin system inhibitor for diabetic kidney disease treatment: an umbrella review of systematic reviews and network meta-analysis - Xue, Xue; Jin, Xin-Yan; Ye, Xing-Lan; Li, Ke-Ying; Li, Jia-Xuan; Liu, Xue-Han; Bai, Juan; Liu, Qiang; Zhang, Bing-Rui; Zou, Xin-Rong; Yuan, Jun; Lu, Chun-Li; et al. (Frontiers in Pharmacology, 2024)
Aims: To synthesize the evidence of the comparative effectiveness and safety of Ophiocordyceps sinensis (OS) preparations combined with renin-angiotensin system inhibitors (RASi) for diabetic kidney disease (DKD).Methods: Eight databases were searched from their inception to May 2023. Systematic reviews (SRs) of OS preparations combined with RASi for DKD were identified. Randomized controlled trials (RCTs) from included SRs and additional searching were performed for data pooling. Cochrane riskof-bias tool (RoB2) and AMSTAR-2 were used to evaluate the methodological quality of RCTs and SRs, respectively. A Bayesian network meta-analysis was performed to compare the add-on effect and safety of OS preparations for DKD. The certainty of evidence was graded by the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) approach.Results: Fourteen SRs were included, whose methodological quality were assessed as high (1/14) or critically low (13/14). After combining additional searching, 157 RCTs were included, involving 13 143 participants. The quality of RCTs showed some concerns (155/157) or high risk (2/157).Jinshuibao capsules and tablets, Bailing capsules and tablets, and Zhiling capsules were evaluated.Compared to RASi, adding either of the five OS preparations was relative to decreased 24 hours urinary total protein. OS preparations ranked differently in each outcome. Jinshuibao capsules plus RASi showed beneficial in reducing urinary protein, serum creatinine, serum urea nitrogen, and blood glucose levels, with moderate-certainty evidence. No serious adverse events were observed after adding OS to RASi.Combining OS preparations with RASi appeared to be associated with decreased urinary protein in DKD patients. Further high-quality studies are needed to confirm.